2021
DOI: 10.1121/10.0004129
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of ship detection and trajectory evaluation using distributed acoustic sensing on an optical fiber telecom cable

Abstract: We detect maritime vessels on a 41.5 km long fiber optic telecom cable using distributed acoustic sensing. We measure noise emitted by the same tanker cruising one day at a distance of 5.7 km from the shore, above 85m of water, and the following day at a distance of 20 km from the shore, above 2000 m of water. The acoustic emissions of the tanker result in measurable strain rate on the optical fiber cable laid on the seafloor and probably, for some sections, covered by sediments. The spectral signature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Rønnekleiv et al (2019) showed that DAS is capable of recording acoustic waves from ships, too. Rivet et al (2021) further explored the potential of this technology to detect and track ships. They concluded that the strain changes in the cable can be caused directly by pressure waves traveling through the water layer or through the sediments for slightly buried sections of the cable.…”
Section: Non-seismic Signals (Ships)mentioning
confidence: 99%
“…Rønnekleiv et al (2019) showed that DAS is capable of recording acoustic waves from ships, too. Rivet et al (2021) further explored the potential of this technology to detect and track ships. They concluded that the strain changes in the cable can be caused directly by pressure waves traveling through the water layer or through the sediments for slightly buried sections of the cable.…”
Section: Non-seismic Signals (Ships)mentioning
confidence: 99%
“…However, the decisive characteristics to classify baleen whales is the spectral content of the signal (McDonald et al, 2006;S ̌irovićet al, 2017). We therefore propose a spatio-spectral representation of the DAS recordings or f-x plot, as employed in (Rivet et al, 2021), to show the spectral signature and its evolution against the distance. The method is detailed in § 4.…”
Section: Changing Perspectives: From Single Point To Distributed Sensingmentioning
confidence: 99%
“…Using an interrogator, DAS technology re-purposes existing dark fiber optic (FO) cables to record nano strain (Culshaw and Kersey, 2008) and has the potential for realtime monitoring over tens of kilometers (up to 171 km (Waagaard et al, 2021)) with a spatial resolution of a few meters (Goertz and Wuestefeld, 2018;Waagaard et al, 2021). Initially applied to geophysical data collection (Schenato, 2017;Hartog et al, 2018), DAS has recently aroused interest with waterborne sound sources, e.g, it has been used for near-surface ship detection and bearing estimation in the Mediterranean sea (Rivet et al, 2021). Quality assessment of the data was performed using controlled airguns sources compared (a) to ocean bottom seismometers recordings in Japan (Matsumoto et al, 2021) and (b) to seismic streamers in Norway (Taweesintananon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…DAS recordings were also used for ambient noise interferometry (e.g., Zeng et al, 2017; E. R. , offering the possibility to retrieve repeatable signals (i.e., Rayleigh and Love waves) for near-surface characterization (E. Dou et al, 2017) and aquifer monitoring (Rodríguez Tribaldos & Ajo-Franklin, 2021). In addition, subsea telecommunication fibers have been used to monitor ocean dynamics (Lindsey et al, 2019;Sladen et al, 2019;Williams et al, 2019Williams et al, , 2022 but also to detect earthquakes (Lior et al, 2021; and acoustic phases (Rivet et al, 2021;Ugalde et al, 2022;, image the near-shore subsurface (Z. J. Spica, Nishida, et al, 2020;Z.…”
Section: Overview Of the Current Fields Of Application In Earth Sciencesmentioning
confidence: 99%